Kernel processing and storage length: effect on the fermentation, nutritional, and physical characteristics of flint corn silage with low DM - Andrade, Marina Elizabeth Barbosa [UNESP]; Messana, Juliana Duarte [UNESP]; Gindri, Marcelo; Gervásio, Jéssica Rocha Sousa [UNESP]; Silva, Matheus Mello [UNESP]; Rabêlo, Carlos Henrique Silveira; Reis, Ricardo Andrade [UNESP] (Elsevier, 2025)
Corn silage (Zea mays L.) is a key forage in dairy and beef production due to its high starch content, which is a major energy source for ruminants. In flint-type hybrids, commonly used in Brazil, starch digestibility is limited by the dense protein matrix (prolamin) surrounding starch granules. This study evaluated the effects of mechanical grain processing during harvest and varying storage lengths on fermentation profile, chemical composition, physical characteristics, and in situ degradability (ISD) of dry matter (DM) and starch in corn silage harvested with less than 30% DM. A flint corn hybrid was harvested using two forage harvesters: one equipped with kernel processing rolls (P-corn) and one without (UP-corn). Forages were chopped to 10mm and ensiled in minisilos for 90, 150, 240, or 360 days. The experiment followed a completely randomized design with repeated measures over time. Kernel processing increased kernel processing score (KPS; +78.2%) and starch ISD (12h; +12%), while reducing concentrations of starch (−16%), prolamin (−18%), and non-protein nitrogen (−33.8%) (P < 0.05). P-corn also had higher values of aNDFom, ADFom, lignin, WSC, and lactic acid, but lower pH, DM losses, effluent, and propionic acid compared to UP-corn (P < 0.05). Storage time affected fermentation dynamics: 1,2-propanediol and acetic acid concentrations increased over time, whereas lactic and propionic acid decreased from 90 to 360 days (P < 0.05). Ammonia-N was higher in P-corn at 240 days but lower than UP-corn at 360 days. Although storage length did not influence starch ISD (12 or 24h), the aerobic stability was improved after 150 days. In , kernel processing enhanced starch availability and fermentation quality, while prolonged storage improved silage stability.